Antiacetylcholinesterase triterpenes from the fruits of Cimicifuga yunnanensis. Issue 14 (19th February 2018) - Nian, Yin; Lu, Ni-Hong; Liu, Xiao-Ling; Li, Da-Shan; Zhou, Lin; Qiu, Ming-Hua
Abstract : Two novel cycloartane triterpenes, cimyunnin E (1 ) and cimicifine B (2 ), were purified from the fruits of Cimicifuga yunnanensis . Significantly, these two compounds showed potent anti -AChE effects and neurotrophic activities. Abstract : Two new cycloartane triterpenes, cimyunnin E (1 ), containing a unique oxaspiro[4.4]nonanedione moiety based on rings D and E, together with cimicifine B (2 ), a 25, 26, 27-trinortriterpene featuring a pyridine ring E, were purified from the fruits of Cimicifuga yunnanensis . Their structures were elucidated by spectroscopic methods and ECD (electronic circular dichroism calculations). Compounds1 and2 showed significant acetylcholinesterase (AChE) inhibition with IC50 values of 1.58 and 3.87 μM, respectively. In addition, they noticeably enhanced the neurite outgrowth of nerve growth factor (NGF) mediated PC12 cells at a concentration of 10 μM.